The Opinions of Teachers on Crisis Management in Guidance Services - Secil Eda Ozkayran; Aslihan Yetis Abali; Ahmet Abali (ÜNİVERSİTEPARK Limited, 2020)
The definition of crisis is a sudden difficulty that occurs in a person's life or at an institution. Negative and spontaneous developments taking place at educational institutions can also be defined as a crisis. The quality of education is determined by the success or failure of crisis management. The basic tasks of guidance services are crisis management and pre-planning crisis intervention in educational settings. Therefore, taking measures against crises in schools and ensuring that they are sustainable is of the utmost importance. In order for this to become more effective, guidance services need to act as a whole; that is, with the school principal, teachers, parents, and also students. The main purpose of this study is to evaluate the attitudes and skills of guidance services, which play a key role in crisis management, according to teachers. The study group of the research consisted of 25 teachers working in high schools in Bartin city center, Turkey, during the 2018-2019 academic year. In determining the working group, the voluntary principle was taken into account. The phenomenology model, one of the qualitative research methods, was used as the basis of the study. As the data collection tool, an interview form was utilized. The data were collected face-to-face, with content analysis technique applied in analyzing the data. The participant teachers' opinions on the crisis management behaviors of guidance services offered within their institution were collected during interview. As a result of the opinions received, the importance and role of guidance services and guidance counselors in crisis management were evaluated.